ICT Delivery Systems' Research Trends In Malaysian Higher Education Institutions: A Content Analysis. - N. Umar, Irfan; Kamal, Nur H.; Jamiat, Nurullizam; Masood, Mona (2009)
Not to be left behind in terms of ICT, Malaysian higher education institutions (HEI) have taken the necessary actions to provide their communities with the appropriate ICT environment.